Finite element analysis of composite concrete-timber beams - N. C. S. FORTI; T. L. D. FORTI; A. E. P. G. A. JACINTHO; L. L. PIMENTEL (Revista IBRACON de Estruturas e Materiais)
AbstractIn the search for sustainable construction, timber construction is gaining in popularity around the world. Sustainably harvested wood stores carbon dioxide, while reforestation absorbs yet more CO2. One technique involves the combination of a concrete slab and a timber beam, where the two materials are assembled by the use of flexible connectors. Composite structures provide reduced costs, environmental benefits, a better acoustic performance, when compared to timber structures, and maintain structural safety. Composite structures combine materials with different mechanical properties. Their mechanical performance depends on the efficiency of the connection, which is designed to transmit shear longitudinal forces between the two materials and to prevent vertical detachment. This study contributes with the implementation of a finite element formulation for stress and displacement determination of composite concrete-timber beams. The deduced stiffness matrix and load vector are presented along to numerical examples. Numerical examples are compared to the analytical equations available in Eurocode 5 and to experimental data found in the literature.